Correlation of Immunoglobulin G With Severity Of Psoriasis - Rukhshan Khurshid; Saima Rasheed; Shakil Ahmed; Huma Ashraf; Gul-; Maira Mahmood (Aziz Fatimah Medical and Dental College, 2023)
Objectives:  To find the correlation of immunoglobulin G with severity of psoriasis. Methodology: This cross-sectional descriptive study was conducted at Sir Ganga Ram Hospital Lahore/Niazi Teaching Hospital Sargodha. Study duration was six months from January 2020 to June 2020. One hundred patients of psoriasis (confirmed by Dermatologist) were included in the study. Questionnaire based on age, gender, duration of illness, type and severity of problem etc and biochemical test including immunoglobulin G were filled by consented patients. The study comprised into patients and controls groups. Fifty age matched Subjects with no history of skin disease were taken as controls. For immunological assessment, IgG was measured by the technique of ELISA. Results: Mean age of developing of disease was in the range of 36 to 43 years. A few patients have family history with a problem of asthma. High severity of index (59 to 61) in both genders with duration of disease was 4 to 6 years. A direct correlation between level of IgG and disease severity was observed. Conclusion: Increased level of immunoglobulin G and its direct correlation with severity of psoriasis may suggest an activation of 2nd immune defense that try to reduce the severity of disease.